Chemical vapor deposition of partially oxidized graphene. Issue 51 (23rd June 2017) - Mutlu, Zafer; Ruiz, Isaac; Wu, Ryan J.; Ionescu, Robert; Shahrezaei, Sina; Temiz, Selcuk; Ozkan, Mihrimah; Mkhoyan, K. Andre; Ozkan, Cengiz S.
Abstract : Mutlu et al. reported on chemical vapor deposition (CVD) of partially oxidized graphene films on copper foils under near-atmospheric pressure. Abstract : Herein, we report on chemical vapor deposition (CVD) of partially oxidized graphene (POG) films on electropolished polycrystalline copper foils at relatively low temperature under near-atmospheric pressure. The structural, chemical, and electronic properties of the films are studied in detail using several spectroscopic and microscopic techniques. The content of carbon and oxygen in the films is identified by chemical mapping at near-atomic scale. Electron diffraction patterns of the films possess clear diffraction spots with a six-fold pattern that is consistent with the hexagonal lattice. The fine structure of the carbon K-edge signal in STEM-EELS spectra of the films is distinguishable from that of graphene and graphite. The presence of oxygen in the films is further supported by a clear oxygen K-edge. Raman spectroscopy and XPS results provide direct evidence for a lower degree of oxidation. The work function of the films is found to be much higher than that of graphene, using UPS measurements.